BENTUK GARAPAN TARI PIRING LAMPU TOGOK KREASI SANGGAR LUBUAK NAN TIGO KOTA SOLOK - Izaty, Rahmi; Nerosti, Nerosti (SENDRATASIK UNP, 2019)
AbstractThis study aims to describe and analyze the forms of creation of Tari Piring Lampu Togok at Lubuak Nan Tigo Studio.This type of research was qualitative research with descriptive analytical methods. The main instruments in this study were the researchers themselves and assisted with supporting instruments including stationery, photo cameras and video cameras. The type of data used primary data and secondary data. Data collection techniques were carried out by means of library studies, observation, interviews and documentation. The steps in analyzing data were collecting the data, analyzing data, describing data and makingconclusions.The results of the study showed that the Tari Piring Lampu Togok was a creative dance by Lubuak Nan Tigo studio, arranged based on the dance movements of the traditional Tari Lampu Togok. The creation of the dance production resulteda quality form of work, including: (1) Motion, consists of: (a) opening motions are anta lampu,puta duduak, tagak itiak, duduak maagah piriang, pitungguang ayun piriang, then (b) core movements are ramo-ramo bagaluik, tupai bagaluik, tusuak muko balakang, usuak bawah ateh, simpia tagak, ayun rang mudo, tusuak mangayun, tupai bagaluik jantan, lenggok basamo, tusuak baganti, piriang manabeh tagak, piriang manabeh duduak, langkah puta ramo-ramo, tusuak sasampiang, simpia duduak, ayun ampek panjuru, next (c) the closing motion isputa habih. (2) Varied floor patterns, namely diagonal, triangle, letter V, letter W, circle and horizontal. (3) Accompanying music uses a musical instrument called tambua, talempong, canang, tasa, bansi, sarunai. (4) male dancers weartaluak balango, galembong pants, deta wrapped in batik cloth andsongket Silungkang andÂ  the costumes for female dancers wear baju kurung, pants, songketSilungkang, and tanduak wrapped in songket. (5) Female dancers wear beautiful makeup and male dancers wear foundation and powder only. (6) Dancer consists of 6 people;3 female dancers and 3 male dancers.Dancers are able to express their movements by maintaining balance and compactness swiftly so that Lampu Togok stands firmly on the headduring the performance. (7) Property is Lampu Togokitself which used to be a light for the community. The lights are turned on using kerosene.The balance ofTari Piring Lampu Togoksymbolizes caution in facing opponents and living life. The compactness of the Tari Piring Lampu Togok symbolizes the community and togetherness in living life.Â Keyword: Solok, Lubuak Nan Tigo Studio, Tari Piring Lampu Togok, Form of Creation.